Accompany singularity in a federal project of performance - Case of the French Triathlon Federation - Bignet, F.; Maze, B. (Science + Triathlon 2015 World Conference, 2015)
A sports federation is an institution that is built to unite other associations and governed by internal and external rules. It has, among other things, the task of contributing to the influence of France abroad through the results of his national team. Since 2009, F.F.TRI has upgraded its vision on how accompanying «identified athletes» in order to create conditions of the emergence of the performance. This new look is based on similar fundamentals to those used by companies where work organizations generate innovation. Innovation is one of the main factor of success, of growing a business. How to incorporate these guidelines in an institutional scheme? How to establish a synergy and not a power struggle between an institution and his athletes? These are just one of the issues to be resolved in everyday life. The presentation will return after the Beijing Olympic Games in 2008 to expose this organizational strategy and how the Federation do concretely to make it operational. Our guideline is described in four major areas in the last two Olympics: valorize performance, only establish performance as a filter for our decisions, accepting the singularity as a source of performance, and dissociate the accompanying process of the evaluation process. This human experience refers to a permanent dilemma between the desire to establish a framework and the creation of individual freedom spaces. Finally, we simply need to understand and accept that person belongs to nobody and that success lies in the alignment of individual`s ambition to become a shared and meaningful ambition.